A method for preparing positive electrode material of carbon dioxide sensing friction nanogenerator

The gel network is formed by the cross -linking of nano cellulose and polyethylene amine, and combined with emulsion and dried film to prepare carbon dioxide sensing with porous structure to friction nano -generator positive pole material, which solves the complexity and complexity of the existing materials preparation process The problem of insufficient sensitivity realizes the efficient and quantitative detection of carbon dioxide.

CN116376097BActive Publication Date: 2025-01-28GUANGXI UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310299096.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-24
Publication Date
2025-01-28
Estimated Expiration
2043-03-24

AI Technical Summary

Technical Problem

The existing carbon dioxide sensing friction nanogenerator electrode materials have complex preparation processes, unfriendly environments, and lack of pore structure, resulting in insufficient sensitivity to carbon dioxide.

Method used

The gel network is used to use nano -cellulose and polyethylene amine static electricity to form a gel network, combined with mechanical decentralization to prepare nano cellulose micro -gel, and pour dry film through lotion to obtain carbon dioxide sensor with porous structure. Essence

Benefits of technology

This material has good porous performance and high ratio of surface area, which significantly improves the adsorption and sensitivity to carbon dioxide gas, and achieves quantitative detection of carbon dioxide.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for preparing a positive electrode material of a carbon dioxide sensing friction nanogenerator, the method comprising the following steps: (1) preparing a nanocellulose / polyethyleneimine microgel colloid using a nanocellulose and polyethyleneimine aqueous solution; (2) mixing the microgel colloid of step (1) with n-hexane in a certain proportion, and subjecting the mixture to high-speed shearing treatment to obtain a film-forming liquid; (3) casting and drying the film-forming liquid to form a film to obtain a positive electrode material of a carbon dioxide sensing friction nanogenerator. The material obtained by the method of the invention has a multi-level pore structure and has good adsorption of carbon dioxide. The material is used as a triboelectric positive material and a perfluoroethylene-propylene copolymer film as a negative electrode material to form a friction nanogenerator. Different electrical signals can be generated when the carbon dioxide concentration changes during the contact separation process, thereby realizing quantitative detection of carbon dioxide. In addition, the method of the invention has a simple preparation process, and the raw materials have good biocompatibility. The obtained material has important application value in the field of gas sensing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparing carbon dioxide gas detection materials, and in particular is a method for preparing a positive electrode material of a carbon dioxide sensing friction nanogenerator. Background Art

[0002] Carbon dioxide sensors are widely used in agriculture, industry, national defense, environmental protection, aerospace and other fields. The core component of carbon dioxide sensors is carbon dioxide sensitive materials. Traditional carbon dioxide sensitive materials are mainly oxide semiconductors and solid electrolytes. There are problems such as the need for external power supply, long response time, and easy pollution of the environment by raw materials, which to a certain extent limit the application scope of such sensors. In recent years, a variety of gas sensors have been developed based on friction nanogenerators, such as Chinese patent application publication numbers CN113791124A, CN113008945B, CN111208170A and CN110868098A. Such sensors have the advantages of no need for external power supply, environmental friendliness, simple process and low price, and are the development trend of gas sensing in the future.

[0003] The working principle of the gas sensor based on the friction nanogenerator is to use the fact that changes in gas concentration will change the electronegativity of the friction surface of the sensing material, causing it to change the surface charge density when it comes into contact with another friction material, thereby affecting the electrical output performance of the generator. By detecting the changes in the electrical signal of the friction nanogenerator under different gas concentrations, quantitative detection of the gas can be achieved. Therefore, the development of friction nanogenerator electrode materials with excellent gas sensitivity is the key to achieving gas sensing with this technology. However, the raw materials for the electrode materials of gas sensing friction nanogenerators are often metal oxides or metal-organic framework materials, which have problems such as complex preparation processes and unfriendly environment. In addition, the above-mentioned electrode materials are mostly based on flexible membranes in structure, lack pore structures, and have a low specific surface area.

[0004] The small area and fewer gas adsorption sites limit the sensitivity of the electrode material to the target gas to a certain extent. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a new method for preparing the positive electrode material of a carbon dioxide sensing friction nanogenerator. The raw materials used in the method are green and environmentally friendly, and the process is simple. The product obtained by the method has a multi-level pore structure and has good adsorption capacity for carbon dioxide. The method is used as a friction positive material and a perfluoroethylene propylene copolymer film as a negative plate material to form a friction nanogenerator. During the contact and separation process, different electrical signals can be generated when the carbon dioxide concentration changes, thereby realizing quantitative detection of carbon dioxide.

[0006] The present invention solves the above technical problems with the following technical solutions:

[0007] The present invention provides a method for preparing a positive electrode material of a carbon dioxide sensing friction nanogenerator, comprising the following steps:

[0008] (1) Preparing nanocellulose / polyethyleneimine microgel colloid: dispersing nanocellulose in deionized water to prepare a nanocellulose aqueous dispersion with a mass concentration of 1.0%; adding a polyethyleneimine aqueous solution with a mass concentration of 2.0% on the nanocellulose aqueous dispersion in an equal volume ratio, and standing at room temperature for 24 hours to obtain a gel matrix; transferring the gel matrix to a polyethyleneimine aqueous solution with a mass concentration of 2.0%, soaking and aging for 12 hours, then taking out and rinsing twice with deionized water of the same mass ratio to obtain a nanocellulose / polyethyleneimine hydrogel; adding deionized water of the same mass ratio to the nanocellulose / polyethyleneimine hydrogel, treating at a mechanical shear rate of 10000 r / min for 5 minutes to obtain a nanocellulose / polyethyleneimine microgel colloid;

[0009] (2) preparing a membrane-forming liquid: placing the nanocellulose / polyethyleneimine microgel colloid obtained in step (1) in a beaker, adding n-hexane dropwise to the nanocellulose / polyethyleneimine microgel colloid using a pipette at a speed of 300 r / min, and after the dropwise addition, using a high-speed disperser at a speed of 12000 r / min for high-speed emulsification for 5 minutes to obtain a membrane-forming liquid; wherein the amount of microgel colloid and n-hexane used is in a weight ratio of 10 to 30 parts: 70 to 90 parts;

[0010] (3) Preparation of carbon dioxide sensing friction nanogenerator positive electrode material: pouring the film-forming solution prepared in step (2) into a polytetrafluoroethylene mold and drying at room temperature to obtain a carbon dioxide sensing friction nanogenerator positive electrode material.

[0011] In the step (1), the surface carboxyl content of the nanocellulose is 0.4-1.2 mmol / g, the diameter of the nanocellulose is 20-100 nm, and the length is 200-2000 nm; the molecular weight of the polyethyleneimine aqueous solution is 10 kDa-70 kDa.

[0012] In the step (1), the polyethyleneimine aqueous solution is added at a rate of 1 mL / min.

[0013] In the step (3), the room temperature drying is performed in a fume hood and dried to a constant weight.

[0014] The present invention utilizes the electrostatic crosslinking of the carboxyl groups on the nanocellulose with good biocompatibility and the amino groups on the polyethyleneimine to form a gel network, combines mechanical dispersion to prepare nanocellulose microgel, and further uses the microgel as a solid particle emulsifier to disperse n-hexane in water to prepare an oil-in-water emulsion as a film-forming liquid. The film-forming liquid has extremely high stability. During the pouring and drying film-forming process, the microgel particles on the droplet interface are crosslinked to form a three-dimensional network skeleton, which gives the electrode material good porous properties and a high specific surface area, which is conducive to the adsorption of gas molecules to improve the sensitivity of the electrode material to carbon dioxide gas. At the same time, the polyethyleneimine on the electrode material provides a chemical adsorption site for carbon dioxide. After the electrode material adsorbs carbon dioxide gas, the surface electron distribution changes, which in turn causes the electrical signal generated during the operation of the friction nanogenerator to change, thereby realizing the quantitative detection of carbon dioxide, and providing a new method for preparing the positive electrode material of the carbon dioxide sensing friction nanogenerator with high efficiency and environmental protection.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] 1) The material obtained by the preparation method of the present invention contains a porous structure, has a large adsorption capacity for carbon dioxide gas, and has high sensitivity as a positive electrode material for carbon dioxide sensing friction nanogenerator. The present invention uses the carboxyl groups on nanocellulose and the amino groups on polyethyleneimine to form a gel network for electrostatic crosslinking to prepare microgels, and further uses the microgel as a solid particle emulsifier to disperse n-hexane in water to prepare an oil-in-water emulsion as a film-forming liquid. The film-forming liquid has extremely high stability, good porous properties and a high specific surface area, which is conducive to the adsorption of gas molecules. The polyethyleneimine on the prepared positive electrode material provides a chemical adsorption site for carbon dioxide, thereby giving the positive electrode material good sensitivity to carbon dioxide gas.

[0017] 2) The preparation method of the present invention is simple in process, environmentally friendly and efficient. The carbon oxide sensing friction nanogenerator positive electrode material with a porous structure can be directly obtained by emulsion casting and drying film formation, and the operation is simple.

[0018] 3) The preparation method of the present invention uses nanocellulose to prepare triboelectric positive electrode materials. The material is green and environmentally friendly, has a wide range of sources, has excellent biodegradability, and can effectively reduce the generation of non-degradable waste. DETAILED DESCRIPTION

[0019] The technical solution of the present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments, and any improvements and changes made on the basis of the present invention are within the protection scope of the present invention.

[0020] Example 1

[0021] A method for preparing a positive electrode material of a carbon dioxide sensing friction nanogenerator comprises the following steps:

[0022] (1) Preparation of nanocellulose / polyethyleneimine microgel colloid: Nanocellulose with a surface carboxyl content of 1.2 mmol / g is dispersed in deionized water to prepare a nanocellulose aqueous dispersion with a mass concentration of 1.0%; a polyethyleneimine aqueous solution with a mass concentration of 2.0% is added on top of the nanocellulose aqueous dispersion at an equal volume ratio at a rate of 1 mL / min, and the mixture is allowed to stand at room temperature for 24 hours to obtain a gel matrix; the gel matrix is ​​transferred to a polyethyleneimine aqueous solution with a mass concentration of 2.0% and soaked for aging for 12 hours, then taken out and rinsed twice with deionized water of an equal mass ratio to obtain a nanocellulose / polyethyleneimine hydrogel; deionized water of an equal mass ratio is added to the nanocellulose / polyethyleneimine hydrogel, and the mixture is treated at a mechanical shear rate of 10,000 r / min for 5 minutes to obtain a nanocellulose / polyethyleneimine microgel colloid; wherein the nanocellulose has a diameter of 20 to 100 nm and a length of 200 to 2000 nm; and the polyethyleneimine has a molecular weight of 10 kDa;

[0023] (2) preparing a membrane-forming liquid: placing the nanocellulose / polyethyleneimine microgel colloid prepared in step (1) in a beaker, adding n-hexane dropwise to the nanocellulose / polyethyleneimine microgel colloid using a pipette at a speed of 300 r / min, and after the dropwise addition, using a high-speed disperser at a speed of 12000 r / min for high-speed emulsification for 5 min to obtain a membrane-forming liquid; wherein the microgel colloid and n-hexane are used in a weight ratio of 20 parts:80 parts;

[0024] (3) Preparation of carbon dioxide sensing friction nanogenerator positive electrode material: pour the film-forming solution prepared in step (2) into a polytetrafluoroethylene mold, dry it in a fume hood at room temperature to constant weight, and obtain a carbon dioxide sensing friction nanogenerator positive electrode material.

[0025] The product prepared in this example has a porous structure. It is used as the positive electrode material of the triboelectric nanogenerator, which can generate different electrical signals when the carbon dioxide concentration changes. Under the test environment of carbon dioxide concentration of 400ppm, 1000ppm, and 2000ppm, the triboelectric nanogenerator composed of perfluoroethylene propylene copolymer film as the negative electrode material is tested for contact and separation, and the output voltages are measured to be 45.57V, 56.33V, and 72.17V, respectively. It can be seen that with the increase of carbon dioxide concentration, the output voltage gradually increases, showing good carbon dioxide sensing performance.

[0026] Example 2

[0027] A method for preparing a positive electrode material of a carbon dioxide sensing friction nanogenerator comprises the following steps:

[0028] (1) Preparation of nanocellulose / polyethyleneimine microgel colloid: Nanocellulose with a surface carboxyl content of 0.4 mmol / g is dispersed in deionized water to prepare a nanocellulose aqueous dispersion with a mass concentration of 1.0%; a polyethyleneimine aqueous solution with a mass concentration of 2.0% is added to the nanocellulose aqueous dispersion at a rate of 1 mL / min in an equal volume ratio, and the mixture is allowed to stand at room temperature for 24 hours to obtain a gel matrix; the gel matrix is ​​transferred to a polyethyleneimine aqueous solution with a mass concentration of 2.0%, immersed and aged for 12 hours, and then taken out and rinsed twice with deionized water of an equal mass ratio to obtain a nanocellulose / polyethyleneimine hydrogel; deionized water of an equal mass ratio is added to the nanocellulose / polyethyleneimine hydrogel, and the mixture is treated at a mechanical shear rate of 10,000 r / min for 5 minutes to obtain a nanocellulose / polyethyleneimine microgel colloid; wherein the nanocellulose has a diameter of 20 to 100 nm and a length of 200 to 2000 nm; and the polyethyleneimine has a molecular weight of 70 kDa;

[0029] (2) preparing a membrane-forming liquid: placing the nanocellulose / polyethyleneimine microgel colloid obtained in step (1) in a beaker, adding n-hexane dropwise to the nanocellulose / polyethyleneimine microgel colloid using a pipette at a speed of 300 r / min, and after the dropwise addition, using a high-speed disperser at a speed of 12000 r / min for high-speed emulsification for 5 min to obtain a membrane-forming liquid; wherein the microgel colloid and n-hexane are used in a weight ratio of 30 parts:70 parts;

[0030] (3) Preparation of carbon dioxide sensing friction nanogenerator positive electrode material: pour the film-forming solution prepared in step (2) into a polytetrafluoroethylene mold, dry it in a fume hood at room temperature to constant weight, and obtain a carbon dioxide sensing friction nanogenerator positive electrode material.

[0031] The product prepared in this example has a porous structure. It is used as the positive electrode material of the triboelectric nanogenerator, which can generate different electrical signals when the carbon dioxide concentration changes. Under the test environment of carbon dioxide concentration of 400ppm, 1000ppm, and 2000ppm, the triboelectric nanogenerator composed of perfluoroethylene propylene copolymer film as the negative electrode material is tested for contact separation power generation. The measured output voltages are 60.11V, 72.48V, and 98.71V, respectively. It can be seen that with the increase of carbon dioxide concentration, the output voltage gradually increases, showing good carbon dioxide sensing performance.

[0032] Example 3

[0033] A method for preparing a carbon dioxide sensing friction nanogenerator positive electrode material comprises the following steps:

[0034] (1) Preparation of nanocellulose / polyethyleneimine microgel colloid: Nanocellulose with a surface carboxyl content of 0.8 mmol / g is dispersed in deionized water to prepare a nanocellulose aqueous dispersion with a mass concentration of 1.0%; a polyethyleneimine aqueous solution with a mass concentration of 2.0% is added at a rate of 1 mL / min on top of the nanocellulose aqueous dispersion in an equal volume ratio, and the mixture is allowed to stand at room temperature for 24 hours to obtain a gel matrix; the gel matrix is ​​transferred to a polyethyleneimine aqueous solution with a mass concentration of 2.0% and soaked for aging for 12 hours, then taken out and rinsed twice with deionized water of an equal mass ratio to obtain a nanocellulose / polyethyleneimine hydrogel; deionized water of an equal mass ratio is added to the nanocellulose / polyethyleneimine hydrogel, and the mixture is treated at a mechanical shear rate of 10,000 r / min for 5 minutes to obtain a nanocellulose / polyethyleneimine microgel colloid; wherein the nanocellulose has a diameter of 20 to 100 nm and a length of 200 to 2000 nm; and the polyethyleneimine has a molecular weight of 25 kDa;

[0035] (2) preparing a membrane-forming liquid: placing the nanocellulose / polyethyleneimine microgel colloid prepared in step (1) in a beaker, adding n-hexane dropwise to the nanocellulose / polyethyleneimine microgel colloid using a pipette at a speed of 300 r / min, and after the dropwise addition, using a high-speed disperser at a speed of 12000 r / min for high-speed emulsification for 5 min to obtain a membrane-forming liquid; wherein the microgel colloid and n-hexane are used in a weight ratio of 10 parts:90 parts;

[0036] (3) Preparation of carbon dioxide sensing friction nanogenerator positive electrode material: pour the film-forming solution prepared in step (2) into a polytetrafluoroethylene mold, dry it in a fume hood at room temperature to constant weight, and obtain a carbon dioxide sensing friction nanogenerator positive electrode material.

[0037] The product prepared in this example has a porous structure. It is used as the positive electrode material of the friction nanogenerator, which can generate different electrical signals when the carbon dioxide concentration changes. Under the test environment of carbon dioxide concentration of 400ppm, 1000ppm, and 2000ppm, the friction nanogenerator composed of perfluoroethylene propylene copolymer film as the negative electrode material is tested for contact separation power generation. The measured output voltages are 53.59V, 63.35V, and 87.66V, respectively. It can be seen that with the increase of carbon dioxide concentration, the output voltage gradually increases, showing good carbon dioxide sensing performance.

Claims

1. A method for preparing a positive electrode material of a carbon dioxide sensing friction nanogenerator, characterized in that: The steps are as follows: (1) Preparation of nanocellulose / polyethyleneimine microgel colloid: Nanocellulose with a surface carboxyl content of 0.4 to 1.2 mmol / g is dispersed in deionized water to prepare a nanocellulose aqueous dispersion with a mass concentration of 1.0%; a polyethyleneimine aqueous solution with a mass concentration of 2.0% is added on top of the nanocellulose aqueous dispersion in an equal volume ratio, and the mixture is allowed to stand at room temperature for 24 hours to obtain a gel matrix; the gel matrix is ​​transferred to a polyethyleneimine aqueous solution with a mass concentration of 2.0%, immersed and aged for 12 hours, and then taken out and rinsed twice with deionized water of the same mass ratio to obtain a nanocellulose / polyethyleneimine hydrogel; deionized water of the same mass ratio is added to the nanocellulose / polyethyleneimine hydrogel, and the mixture is treated at a mechanical shear rate of 10,000 r / min for 5 minutes to obtain a nanocellulose / polyethyleneimine microgel colloid; the surface carboxyl content of the nanocellulose is 0.4 to 1.2 mmol / g; (2) preparing a membrane-forming liquid: placing the nanocellulose / polyethyleneimine microgel colloid prepared in step (1) in a beaker, adding n-hexane dropwise to the nanocellulose / polyethyleneimine microgel colloid using a pipette at a speed of 300 r / min, and after the dropwise addition, using a high-speed disperser at a speed of 12000 r / min for high-speed emulsification for 5 minutes to obtain a membrane-forming liquid; wherein the microgel colloid and n-hexane are used in a weight ratio of 10 to 30 parts: 70 to 90 parts; (3) Preparation of carbon dioxide sensing friction nanogenerator positive electrode material: pouring the film-forming solution prepared in step (2) into a polytetrafluoroethylene mold and drying at room temperature to obtain a carbon dioxide sensing friction nanogenerator positive electrode material.

2. The method for preparing the positive electrode material of the carbon dioxide sensing friction nanogenerator according to claim 1, characterized in that: In step (1), the nanocellulose has a diameter of 20 to 100 nm and a length of 200 to 2000 nm; and the molecular weight of the polyethyleneimine aqueous solution is 10 kDa to 70 kDa.

3. The method for preparing the positive electrode material of the carbon dioxide sensing friction nanogenerator according to claim 1, characterized in that: In step (1), the polyethyleneimine aqueous solution is added at a rate of 1 mL / min.

4. The method for preparing the positive electrode material of the carbon dioxide sensing friction nanogenerator according to claim 1, characterized in that: Step (3), the room temperature drying is performed in a fume hood, and the drying is performed to a constant weight.

Citation Information

Patent Citations

  • Self-powered ammonia gas sensing friction nano-generator and preparation method and application thereof

    CN110868098A

  • Passive ammonia gas sensor based on electron-withdrawing polymer film

    CN111208170A

  • A triboelectric nanogenerator-driven micro gas detection system, its preparation method and application

    CN113008945B

  • NO2 gas monitoring system driven by wind power friction nano-generator and preparation method and application of NO2 gas monitoring system

    CN113791124A

  • Preparing method for amido-modified nanometer fiber material for carbon dioxide adsorption

    CN106283660A